Energy efficiency and indoor climatic conditions in buildings: dynamic modeling for systemic improvement - Bilous, Inna; Biriukov, Dmytro; Eutukhova, Tatiana; Novoseltsev, Oleksandr; Voloshchuk, Volodymyr; Prozuments, Aleksejs (Frontiers in Built Environment, 2025)
Improving the comfort of living and/or working conditions in buildings usually requires an increase in the consumption of energy and building materials, e.g., for thermal modernization, and thus additional economic costs. It is also important to note that this does not always lead to a reduction in overall emissions of pollutants into the environment, taking into account emissions at all stages of the production and use of energy and materials for energy efficiency and comfort in buildings. The paper is devoted to the problems of modelling energy supply systems for buildings, including methods and means of simulating thermal regimes of buildings and their engineering systems, as well as methods and means of modelling the operating modes of heat pumps that can be used in such systems for a coordinated improvement of energy efficiency and indoor climatic conditions in buildings. Based on the developed mathematical models, the dynamic modes of building energy supply systems are studied and recommendations for improving their efficiency are given. The dynamic models of the energy supply system is implemented in the MATLAB/Simscape software environment and the possibilities (schemes) of detailing the components of different types of sources are shown. The obtained results were verified by means of energy models created in the widely used software product EnergyPlus. It was found that, according to the quasi-steady-state method, the deviation of the energy consumption does not exceed 13% and is about 5% in dynamic modes. The possibilities of using a gas boiler and a heat pump as the most common sources of individual energy supply systems for buildings are investigated. It was found that the heat pump has a more flexible load level control. Its use can reduce the instantaneous power value by up to 40%, but the frequency of switching on the pump is much higher (about 4 times) compared to the gas boiler. If the energy sources produce the same amount of energy, the heat pump keeps the temperature within the set range more efficiently, avoiding overheating. In general, the presented energy dynamic building model and its software implementation allow a wide range of researchers to simulate different energy supply systems to ensure proper energy efficiency and indoor climate in a building.